O desempenho do programa nacional de fortalecimento da agricultura familiar no estado do Rio Grande do Sul - Haag, Áureo Leandro (2009)
Since its creation, the National Program for Strengthening Family Farming (PRONAF) has been the main public policy for the inclusion of the family farmers into the formal agricultural credit, such farmers in the past were not even acknowledged as a productive party by the Government. Furthermore, a recent valorization of family farming has taken place in the sense of allowing to fulfill an active role before the new ways of understanding the economic development. Family farmers in Rio Grande do Sul have had a great participation in the program since its implementation. Besides, Family farming has a great economic and social importance. The goal of this dissertation is to verify the logics of the distribution of these resources in the state of Rio Grande do Sul. To do so, a Rural Development Index has been used based on the works of Silva (2006) and mapping techniques. As a result it is observed that, in the case o Rio Grande do Sul, PRONAF is still very connected to banking logics, that is, family farmers who are not well integrated within the market and who would theoretically need a major attention from the government still have great difficulty getting access to these PRONAF resources.